Participatory Heritage On Social Networking Sites: The Discussion of Main Theoretical Concepts - Kelpšienė, Ingrida (Information & Media, 2021)
The field researching cultural heritage communication on social networking sites, is still developing its theoretical foundations, while participatory heritage, as one of the newest concepts born in this field, is still lacking its grounded conceptualization, especially emerging from practice-based research studies. This theoretical study suggests to integrate different theoretical considerations that derives from cultural heritage studies, social networking sites research and theory of participation, and proposes to refine the concept of participatory heritage believing that the primary understanding of the context as “participatory” lies not in the environment itself, but in the activity that takes place in it. Therefore, I offer that participatory heritage could be understood as a new shift in cultural heritage practice that emerge through collaboration and communication of people on social networking sites.